The delirium experience: A review - O'Malley, Gráinne; Leonard, Maeve; Meagher, David; O'Keeffe, Shaun T. (Journal of psychosomatic research, 2008)
While the adverse medical complications and consequences of delirium has been well studied, the same is not true of the psychological morbidity associated with the condition. A better understanding of what it is like to be delirious has the potential to improve recognition, management and treatment of delirium. This article examines the literature relating to the experience of delirium from the perspective of patients, families, and staff. Finally, suggestions for further work that might advance might advance our understanding of these issues are outlined.